2012
DOI: 10.1016/j.celrep.2012.09.024
|View full text |Cite
|
Sign up to set email alerts
|

SAP102 Mediates Synaptic Clearance of NMDA Receptors

Abstract: Summary Membrane-associated guanylate kinases (MAGUKs) are the major family of scaffolding proteins at the postsynaptic density. The PSD-MAGUK subfamily, which includes PSD-95, PSD-93, SAP97 and SAP102, is well accepted to be primarily involved in the synaptic anchoring of numerous proteins, including N-methyl-D-aspartate receptors (NMDARs). Notably, the synaptic targeting of NMDARs depends on the binding of the PDZ ligand on the GluN2B subunit to MAGUK PDZ domains as disruption of this interaction dramaticall… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
59
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 72 publications
(68 citation statements)
references
References 43 publications
9
59
0
Order By: Relevance
“…Cultured cortical neurons were infected with lentivirus expressing a previously characterized SAP102 I1 shRNA that selectively knocked down expression of I1 region-containing SAP102 (16). In previous studies we have shown that I1 regioncontaining SAP102 mediates synaptic removal of GluN2B-containing NMDARs (15). Consistently, we found that surface expression of GluN2B was substantially increased upon knocking down the I1 region-containing SAP102, whereas surface expression of GluN2A was not changed (Fig.…”
Section: Resultssupporting
confidence: 67%
See 2 more Smart Citations
“…Cultured cortical neurons were infected with lentivirus expressing a previously characterized SAP102 I1 shRNA that selectively knocked down expression of I1 region-containing SAP102 (16). In previous studies we have shown that I1 regioncontaining SAP102 mediates synaptic removal of GluN2B-containing NMDARs (15). Consistently, we found that surface expression of GluN2B was substantially increased upon knocking down the I1 region-containing SAP102, whereas surface expression of GluN2A was not changed (Fig.…”
Section: Resultssupporting
confidence: 67%
“…The different mechanisms by which PSD-95 and SAP102 are targeted to synapses suggest that they play distinct roles in receptor stabilization and/or trafficking at synapses. Indeed, SAP102 is highly mobile in dendritic spines compared with PSD-95 and has recently been shown to mediate synaptic removal of GluN2B-containing NMDARs (15). We have now identified an alternatively spliced region I2 between the SH3 and GK domains that is important for SAP102 synaptic targeting, indicating that synaptic localization of SAP102 is regulated by splicing events.…”
Section: Discussionmentioning
confidence: 69%
See 1 more Smart Citation
“…We thus focused on scaffolding proteins at excitatory and inhibitory synapses -PSD95, SAP102 (also known as DLG3) and gephyrin, which in fact act as adaptor proteins for glutamate receptors (PSD95 and SAP102), GABA A and glycine receptors (gephyrin) (Chen et al, 2012;Dumoulin et al, 2009;Lau and Zukin, 2007;Maas et al, 2006;Zheng et al, 2011). To examine whether these scaffolding proteins act as adaptor proteins for FGF22 and FGF7, we performed live-imaging experiments with fluorescent-protein-tagged FGFs and scaffolding proteins.…”
Section: Synaptic Targeting Of the Inhibitory Presynaptic Organizer Fmentioning
confidence: 99%
“…Primary Culture of Hippocampal Neurons and Transfection-Primary hippocampal cultures were prepared from embryonic day 18 (E18) Sprague-Dawley rats as previously described (28). Briefly, hippocampal tissue was dissociated with trypsin and plated on poly-D-lysine-coated coverslips at a density of 2 ϫ 10 6 cells/ml.…”
Section: Methodsmentioning
confidence: 99%